Analysis Of Competitiveness and Determinants of Indonesia’s Fishery Exports in the International Market for the Period 2018–2022 - Yohanes Subanpulo Purunama Lein; I Made Endra Kartika Yudha (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Indonesia ranks second as the world’s largest fishery-producing country. However, this potential contrasts with the relatively small and stagnant contribution of fishery exports to the GDP each year when compared to other export commodities in the agricultural sector. This study aims to determine the export competitiveness of fisheries and the effect of Indonesia’s GDP, the GDP of destination countries, Indonesia’s population growth rate, the population growth rate of destination countries, and economic distance simultaneously and partially on the value of Indonesia’s fishery exports to 20 destination countries. This research uses panel data, consisting of cross-section and time series data for the period 2018–2022. The data analysis technique employs panel data regression with the assistance of the Eviews-12 analysis tool. The results show that Indonesia’s GDP, the GDP of destination countries, Indonesia’s population growth rate, the population growth rate of destination countries, and economic distance simultaneously have an effect on Indonesia’s fishery exports. The population growth rate of destination countries has no effect on fishery exports, while economic distance has a significant negative effect on Indonesia’s fishery exports.